Determination of Chemical Components of Memecylon umbellaltum Burm. - A Medicinal Plant, Karnataka, India - Krishanamurthy, S.R.; Asha, B. (Pakistan Journal of Nutrition, 2010)
Memecylon umbellatum Burm. has been being used not only for treatment of diseases but also for other uses since time immemorial. The different parts of the plant have been used for the preparation of the herbal products which are used orally or for external applications. The leaves of the M. umbellatum which have been collected from Koppa and Bannerghatta are subjected for analysis of proximates, micro, macro and toxic elemental composition. The young and mature leaves are separately analyzed. The study reveals that moisture, carbohydrate and crude protein content are the dominant factors in both the young and mature leaf samples. Whereas, crude fat was followed by ash and crude fiber in both young and mature leaf samples of Koppa and in case of Bannerghatta samples crude fat was followed by crude fiber and ash. However, the young leaves are more nutrient than that of mature in both the cases. Among the macronutrients K was dominant which is followed by Ca, Mg, Na and P in both young and mature leaves of Koppa whereas in case of Bannerghatta samples K was followed by Ca, Mg, P and Na, in young leaves but in mature leaves Ca was followed by K, Mg, Na and P in their concentrations. The Fe was highest among the micronutrients of both young and mature leaves of Koppa and Bannerghatta samples. Fe was followed by Mn, Cu and Zn in case of Koppa samples whereas Fe was followed by Mn, Zn and Cu in young leaves and Fe was followed by Mn, Cu and Zn in mature leaves sample of Bannerghatta. There was a significant variation of Cu among the different leaf samples of Koppa and Bannerghatta samples. The Pb content of the young leaves of Koppa is higher than that of Bannerghatta samples and mature leaves of Bannerghatta samples recorded high values of Pb than that of Koppa samples. Between the 2 toxic elements Pb was higher than that of Cd and the mature leaves of both Koppa and Bannerghatta samples recorded lowest concentration of Cd. The results were subjected for statistical analysis.